Print culture in the Sultanate of Riau-Lingga during the late nineteenth and early twentieth centuries - Zakariya, Hafiz; Oktasari, Wiwin (Asian Research Journal of Arts & Social Sciences, 2019)
Print empowers ways of communicating an idea. In fact, in many ways, it could promote democratization of an individual’s expression, which sometimes can be uncontrollable and even anarchic. Though printing has powerful impact on society; it has been ignored in mainstream scholarship. Existing studies about printing press and its impact on the Malay world are limited. It is surprisingly marginalized in the mainstream scholarship despite the fact that history actually bears witness that printing played an important role in the past. Thus, this article discusses the print culture in the Malay world with special reference to the Kingdom of Riau-Lingga. It begins by describing the techniques of printing especially lithography and typography used in the Malay world. It also explains the advent of the print technology in the Dutch East Indies in general and Riau in particular, and how the print culture gradually replaced manuscript in knowledge transmission during the time of Raja Ali Haji. Subsequently, it describes how the Rushdiah Club utilized this technology during the end of the 19th century in Riau-Lingga.